2019
DOI: 10.1029/2018gl078004
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's Ionosphere: Electron Density Altitude Profiles and D‐Ring Interaction From The Cassini Grand Finale

Abstract: We present the electron density (ne) altitude profiles of Saturn's ionosphere at near‐equatorial latitudes from all 23 orbits of Cassini's Grand Finale. The data are collected by the Langmuir probe part of the Radio and Plasma Wave Science investigation. A high degree of variability in the electron density profiles is observed. However, organizing them by consecutive altitude ranges revealed clear differences between the southern and northern hemispheres. The ne profiles are shown to be more variable and conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 36 publications
(75 reference statements)
6
44
0
Order By: Relevance
“…The fit of the two‐part exponential scale height density model to the RPWS ionospheric electron densities shows a double‐layered Saturn ionosphere for both the northern and southern hemispheres. The low‐altitude layer below 4,500 km is similar in both the northern and southern hemispheres with derived scale heights of 545 and 575 km, respectively, in agreement with the scale height at similar altitudes for the Final Plunge (Hadid, Morooka, Wahlund, Persoon, et al, ). It is also similar to the value of 500 km from earlier dusk radio occultation observations (Nagy et al, ).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The fit of the two‐part exponential scale height density model to the RPWS ionospheric electron densities shows a double‐layered Saturn ionosphere for both the northern and southern hemispheres. The low‐altitude layer below 4,500 km is similar in both the northern and southern hemispheres with derived scale heights of 545 and 575 km, respectively, in agreement with the scale height at similar altitudes for the Final Plunge (Hadid, Morooka, Wahlund, Persoon, et al, ). It is also similar to the value of 500 km from earlier dusk radio occultation observations (Nagy et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…The orbit‐to‐orbit variability may be due to longitudinal differences in the orbits, especially at higher latitudes. But a strong contributing factor leading to temporal electron density variations is likely to be the dynamic nature of Saturn's ionosphere and the ring‐ionosphere interaction (Hadid, Morooka, Wahlund, Persoon, et al, ). Variability in the photolytic processes acting on the ring atmosphere and ionosphere and/or meteoroid impacts on the ring surface could cause temporal changes in the electron density through these interactions.…”
Section: Rpws Electron Density Distributions In Saturn's Ionospherementioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to asymmetric current systems caused by seasonal effects. Indeed, Hadid, Morooka, Wahlund, Persoon, et al () found more pronounced ring‐planet electrodynamic interactions in the southern hemisphere during the Grand Finale orbits. Future results by the magnetometer instrument onboard Cassini will shed light on the large‐scale current system at Saturn, particularly during the Grand Finale orbits.…”
Section: Discussionmentioning
confidence: 99%